The International Criminal Court and the principle of complementarity: a comparison of the situation in the Democratic Republic of the Congo and the situation in Darfur - Koen, Raymond (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.